Melphalan improves toxicity of arsenic trioxide in adult T-cell leukemia/lymphoma cells - Khodadadi, Faeze; Sadeghian, Mohammad Hadi; Delbari, Zahra; Kazemi, Mohadese; Koohpaykar, Hamide; Rassouli, Fatemeh B. (Biochemistry and biophysics reports, 2025)
Adult T-cell leukemia/lymphoma (ATLL) is a hematologic neoplasm with poor prognosis. Melphalan is an alkylating anti-cancer agent, and arsenic trioxide (ATO) is routine chemotherapy drug for ATLL with low response rate. Due to the significant challenge that chemoresistance poses in treating ATLL, we aimed to investigate the potential of melphalan to enhance the effects of ATO as a combinatorial treatment approach for ATLL. MT-2 cells were exposed to different concentrations of melphalan and ATO and viability was evaluated by alamarBlue assay. Upon IC50 determination, cells were treated with 0.5 μg/ml melphalan and 2 μM ATO for 72 h, and changes induced on the cell cycle were analyzed by PI staining and flow cytometry, while the expression of candidate genes was assessed by quantitative PCR. For in silico analysis, the expression of ABCG2 was assessed in MT-2 cells and ATLL subtypes using GEO database, and molecular docking was performed to predict the interaction of melphalan with this drug transporter. Melphalan enhanced the cytotoxicity of ATO up to 32.05 %, and caused accumulation of cells in the sub G1 phase of the cell cycle. Besides, combination of melphalan and ATO induced considerable reduction in c-MYC, BMI-1, CD44 and NF-κB (REL-A) expression. Volcano plots revealed the overexpression of ABCG2 in MT-2 cells and acute and smoldering ATLL subtypes, and molecular docking indicated favorable affinity of melphalan with ABCG2. Current findings provide valuable insights into the mechanism of action of melphalan and highlight the importance of targeting drug transporters in improving chemotherapy efficacy in ATLL. •Melphalan enhances ATO cytotoxicity of ATO in MT-2 cells, aiding ATLL therapy.•The study reveals melphalan induces cell cycle arrest and downregulates c-MYC.•Melphalan interacts with ABCG2, offering insights into overcoming chemoresistance.